The Sharīʿah and the Muslim Feminists’ Public Display of the Female Body - Ibrahim Olatunde Uthman (UIN Sunan Gunung Djati Bandung, 2022)
Muslim feminists in Muslim societies have become increasingly independent and visible professionals in the modern world. They are visible in the public space, especially in the entertainment industry, as they use global information technology to Protectthemselves and their bodies. This raises the question of how Muslim women negotiate Islamic teachings over the visibility of their bodies. Few studies have interrogated this question in the light of Islamic teachings; hence, the need for this study. This paper aims at a detailed examination of the public visibility of Muslim feminists in light of Sharīʿah rulings on the public visibility of male and female bodies. Laura Mulvey’s Hollywood Theory on entertainment spectatorship, as used in her “Visual Pleasure and Narrative Cinema,” is adopted as the theoretical framework to engage the notions of the lustful male gaze and women’s erotic power of fitnah as prevalent in Islamic discourse. In addition, secondary data drawn from extant literature, interviews, and internet sources are used to interrogate the discourse of five purposefully selected Muslim feminists in the context of Sharīʿah rulings on the erotic power of women and their public visibility. The paper concludes that while Islamic teachings discourage the culture of public nudity by both males and females, the inequitable treatment of Muslim feminists regarding their public appearance is at variance with the above Sharīʿah rulings.